ANALISIS KINERJA ORGANISASI KANTOR PERTANAHAN KOTA SEMARANG - Adithya Adam Permana; Dyah Hariani; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Organizational performance is an outcome at the level or organization unit analysis. The performance at this organizational level is related to the organizational goals, organizational design, and organizational management. Badan Pertahanan Nasional (BPN) is non-ministerial governmentagencieswhichis under and responsible to the President. It is conducted by the head office (in accordance with Government Regulation number 10 of 2006). BPN has a duty to carry out government task in the land sector of national, regional, and sectoral. This research will analyze organizational performance anddimensions whether support or impede the organizational performance in Land Office of Semarang. This research uses organization theory and five dimensions of work measurement, which are dimensions of productivity, quality of service, responsiveness, responsibility, andaccountability. Methods of collecting data used by researcher are through interview and documentation with all matters related to the Land Office of Semarang. The result of this research shows that Organizational Performance in Land Office of Semarang is still not optimal. This is happened because there are still found some obstacles on dimensions of productivity, like human resources problem and lack of agrarian socialization to the people, and also the length of time to finish a task. While supporting dimensions of organizational performance in Land Office of Semarang that work well are dimensions ofservice quality, responsiveness, responsibility, andaccountability. To solve the problem, there are some solutions to optimize the organization performance that can be done by Land Office of Semarang like doing education and training to improve the quality of human resources, doing socialization to the people regularly and thoroughly, and adding honorary workers to ease the workload in Land Office of Semarang.